Implementasi media pembelajaran Game Edukatif Berbasis Word Wall Dalam Materi Flora dan Fauna di Indonesia Kelas VI di SDN Mlokorejo 03 - Muna, Fela Faizatul; Prayoga, Muhammad Suwignyo (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2024)
This research aims to implement educational game-based learning media Wordwall in Indonesian flora and fauna material for class VI students at SDN Mlokorejo 03. The increasing need for interesting and interactive learning methods prompted this research to be carried out. The method used is descriptive, which aims to develop and test the effectiveness of educational games in increasing students' understanding of flora and fauna. The research process includes needs analysis, designing Wordwall-based educational games, implementation in the classroom over six meetings, and evaluation of learning outcomes. Data was collected through observation, student knowledge evaluation tests, and questionnaires to measure student responses to the use of this learning media. Data analysis was carried out qualitatively and quantitatively to measure increases in student understanding and acceptance of the methods applied. The research results show that the implementation of Wordwall-based educational games is effective in increasing students' understanding of flora and fauna in Indonesia, with an average increase in test scores reaching 25%. Students responded positively to this learning media, which also helped create a more interactive and enjoyable learning atmosphere.